Pengaruh Kepemimpinan Kepala Sekolah dan Motivasi Kerja terhadap Kompetensi Profesional Guru Sekolah Dasar Negeri - Ulfah, Maria; Murniati, Ngurah Ayu Nyoman; Sudana, I Made (Jurnal Inovasi Pembelajaran di Sekolah, 2023)
Mastery of teachers' professional competency standards is expected to be able to improve their professionalism, the quality of student learning, and the quality of education. Teachers' professional competence is influenced by various factors, two of which are the principal's leadership and work motivation. The demand for a teacher to increase his competence is the main reason for the importance of mastering teacher professional competence. The problems in this research are (1) How does the principal's leadership influence the professional competence of state elementary school teachers in Tonjong District, Brebes Regency? (2) How does work motivation influence the professional competence of state elementary school teachers in Tonjong District, Brebes Regency? (3) What is the influence of the principal's leadership and teacher work motivation on the professional competence of public elementary school teachers in Tonjong District, Brebes Regency? This research aims to analyze the influence of school principal leadership and work motivation both partially and jointly on the professional competence of state elementary school teachers in Tonjong District, Brebes Regency. This research uses quantitative descriptive methods. The population in the study was 267 people, the sample was 160 people. The instrument test used is the validity and reliability test. The classical assumption test uses the normality test, linearity test, multicollinearity test, and homogeneity test. Data analysis used a simple linear regression test, multiple linear regression test, F test (ANOVA) and t test. The results of the research and data processing can be described as follows: 1) Principal leadership has a positive and significant effect on the Professional Competence of Public Elementary School Teachers in Tonjong District Brebes Regency, it was proven that the t test results were 80.714 > t table 1.97490. The correlation between principal leadership and teacher professional competence is 0.976 in the very strong category. The magnitude of the influence of X1 on Y is 97.6%; 2) Work motivation has a positive and significant effect on the professional competence of state elementary school teachers in Tonjong District, Brebes Regency, as proven by the t test results of 68.953 > t table 1.97490. The correlation between teacher work motivation and professional competence is 0.968 in the very strong category. The magnitude of the influence of . This means that the principal leadership variables (X1), work motivation (X2) simultaneously have a significant effect on the teacher professional competency variable (Y) in Tonjong District, Brebes Regency. The simultaneous influence is 97.9% while 2.1% is influenced by other variables. Keywords: Learning Leadership, Work Motivation, Teacher Professional Competence